THE PROGRESSIVE LOW CHRONIC INFLAMMATION ON ORAL TISSUES IN ELDERLY - Zahreni Hamzah; Dyah Indartin; Zahara Meilawaty (UPT Penerbitan Universitas Jember)
Aging is a normal process, as inevitable biologicalphenomenon. Generally, this process characterizedby a decrease in the ability of resolution,regeneration, and reparation of cell and tissues, So,those cells and tissues cannot function properly andits will grow up and die.(1) WHO reports that thepopulation of elderly people worldwide increases by1.7% annually, whereas the population of peopleaged ≥ 65 years old increases by 2.5%. WHOclassified the elderly based on their chronologic/biologic state in 4 groups: (1) the middle age ranged45-59 years old, (2) the older/elderly age ranged 60-74 years old, (3) the advanced old age ranged 75-90years old, and (4) the very old age over 90 years old.Generally, elders ≥ 65 years old have healthproblems as effects of aging process. That meansthey need to have a special concern about theirhealth condition include in dental care.(2,3)Low, systemic and progressive chronic inflammationin elderly age is called inflammaging. This conditioncan occur as the effects of injury on cells andtissues.(4,5) There are some factors that cause injuryon cells, such as; hypoxia, chemical materials (toxins,drugs), physical agents (mechanical trauma,temperature, sudden changes in atmosphericpressure, radiation, electrical potency), microbiologyagents (virus, microbes, fungi), immune systemdisorder, genetic disorder, or malnutrition. Whenthe cells got injuries, there are some possibilityreactions on cells and tissues, e.g. retrogressivereaction, progressive reaction; and adaptationreaction. The main cause and the response towardsinflammaging that linked to illness are stillunknown.(6)